The enhancement of the magnetic properties of α-Fe2O3 nanocatalyst using an external magnetic field for the production of green ammonia - Alqasem, B. (Elsevier Ltd, 2017)
Hematite nanocatalysts with improved magnetic properties were synthesized using electrical resistive heating under the presence of a magnetic field and a gaseous environment containing oxygen and nitrogen. The synthesis temperature was varied from 500–850 °C in the absence and presence of a static magnetic field of 0.25 T. VSM hysteresis results showed that there is a clear improve in the magnetic properties of the nanocatalysts when an external magnetic field was used during the synthesis. It also showed that the nanowires amongst other shapes hold the highest saturation magnetization value. The produced α-Fe2O3 nanocatalysts were used for ammonia synthesis under an external magnetic field strength ranging between 0.4–2 T. Correspondingly, (24.174 mmol h−1 g cat−1) ammonia was yielded by applying an external magnetic field of 1.2 T and using the α-Fe2O3 nanowires synthesized at 700 °C with the highest saturation magnetization value of 189.43 emu/g. © 2016 Elsevier B.V.